(untitled) (Physical Education, Health and Social Sciences, 2025)
Objectives: This study examined the impact of international commercial arbitration treaties on Pakistan’s legal system with a specific focus on the enforcement and recognition of foreign arbitral awards. The primary objective is to analyze how Pakistan’s adherence to international arbitration conventions, such as the New York Convention, 1958 has influenced its domestic legal framework. Additionally, the study aims to identify challenges and opportunities in the implementation of these treaties and their implications for Pakistan’s legal and commercial landscape. Materials and Methods: The research employed a doctrinal legal research methodology which involves the analysis of primary and secondary legal sources. Primary data collected from international arbitration treaties, relevant statutes, related to foreign arbitral awards. Secondary sources encompass scholarly articles, books, and reports on international arbitration and its impact on domestic legal systems. The study also examined application of the New York Convention in Pakistan in perspective of the international commercial arbitration and the Recognition and Enforcement (Arbitration Agreements and Foreign Arbitral Awards) Act 2011. Implication: The findings reveal that Pakistan’s adoption of New York Convention, 1985 has significantly enhanced its legal framework for the enforcement of foreign arbitral awards. However, challenges such as judicial reluctance, procedural delays, and a lack of awareness among legal practitioners persist. The study highlighted the need for legislative reforms, capacity building for the judiciary and increased awareness among stakeholders to fully realize the benefits of international arbitration treaties. Results and Discussion: The analysis demonstrated that international arbitration treaties have contributed to the modernization of Pakistan’s arbitration laws aligning them with global standards. The enforcement of foreign arbitral awards has improved, fostering greater confidence among foreign investors. However, the study identified gaps in the implementation process, including inconsistent judicial interpretations and limited institutional support for arbitration. The discussion emphasizes the importance of addressing these challenges to strengthen Pakistan’s position as an arbitration-friendly jurisdiction.